Elderly Patients Undergoing Minimally Invasive Transforaminal Lumbar Interbody Fusion May Have Similar Clinical Outcomes, Perioperative Complications, and Fusion Rates As Their Younger Counterparts - Goh, Graham Seow-Hng; Tay, You Wei Adriel; Liow, Ming Han Lincoln; Gatot, Cheryl; Ling, Zhixing Marcus; Fong, Poh Ling; Soh, Reuben Chee Cheong; Guo, Chang Ming; Yue, Wai-Mun; Tan, Seang-Beng; Chen, John Li-Tat (Clinical orthopaedics and related research, 2020)
Although several studies have suggested that minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) may be especially beneficial in the elderly population due to lower operative morbidity and faster postoperative recovery, there are limited studies investigating the functional outcomes, quality of life, and satisfaction in elderly patients after MIS-TLIF. Furthermore, existing studies had substantial clinical, diagnostic, and surgical heterogeneity. We asked if elderly patients could experience comparable (1) patient-reported pain, disability and quality of life, (2) perioperative complications, and (3) radiological fusion rates as their younger counterparts after MIS-TLIF. Prospectively collected registry data of patients undergoing primary, single-level, MIS-TLIF for degenerative spondylolisthesis between 2012 and 2014 were reviewed. We included 168 patients, 39 of whom were at least 70 years old. Of the 129 patients younger than 70 years old, propensity-score matching was used to select 39 younger controls with adjustment for sex, BMI, American Society of Anesthesiologists score, and baseline clinical outcomes. Perioperative complications and radiologic data were compared. There was no difference in back pain (mean difference -0.3 [95% confidence interval -1.0 to 0.5]; p = 0.52); leg pain (mean difference -0.1 [95% CI to 0.6-0.5]; p = 0.85); Oswestry Disability Index (mean difference -2.9 [95% CI -8.0 to 2.2]; p = 0.26); and SF-36 physical (mean difference 3.0 [95% CI -0.7 to 6.8]; p = 0.107); and mental component summary (mean difference 1.9 [95% CI -4.5 to 8.2]; p = 0.56); up to 2 years postoperatively; 85% of younger patients and 85% of elderly patients were satisfied (p > 0.99) while 87% and 80%, respectively, had fulfilled expectations (p = 0.36). Four perioperative adverse events occurred in each group. There was also no difference in the rate of fusion (87% in younger patients and 90% in elderly patients; p = 0.135). When clinical and surgical heterogeneity were minimized, elderly patients undergoing minimally invasive transforaminal lumbar interbody fusion not only had comparable rates of perioperative complications but also experienced similar improvements in pain, function, and quality of life. A high rate of satisfaction was achieved. Level II, prognostic study.